School of Nature : Alternative Education For Students In 21 Century Life Skills - Nanda Ayu Setiawati; Elvi Mailani; Fadhilla Syam Nst; Edy Surya (Journal of Education and Teaching Learning, 2022)
These 21st century skills need to be developed from an early age through education so that students can live decently in a global society for productive years. The Faculty of Natural Sciences is used as an alternative for life skills education in the 21st century. The purpose of this research is to equip the Indonesian people, especially the government, educators, students and child observers about the importance of child-friendly schools and JIGS Medan in providing educational facilities to students who attend 21. This is to educate about the existence of the school of nature. Century life skills. This survey is an interpretive qualitative survey. In this study, primary data from observations and interviews at Natural School were obtained from observations and interviews at JIGS Natural School Medan, and secondary data from literature studies. The procedure is as follows: Data reduction, data model, conclusion, validation. As a result of research, this well-presented concept provides Sekolah Alam as a child-friendly school solution consisting of anti-bullying programs such as Network People and Nursing, which are implemented in almost all natural schools, for example. worth it. This is a kid friendly concept.